Effect of Emotional Intelligence Training Program on Critical Thinking Skills and Self-Esteem of Nurse Students - Neama Elnouby Ali Ahmed; Samia Mohamed Abdallah Adam; Rabab Mahmud Hassan Mohamed (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Emotional intelligence is an important aspect at work and life that can leads people to effectively think and act toward any situations they face which affect their self - esteem.Aim: This study aims at measuring the effect of emotional intelligence training program on critical thinking skills and self-esteem of nurse students.Design: A quasi-experimental design was used.Setting: The study was conducted at Abbassia school of Nursing for girls.Subject: all third year nurse students. Their total number is sixty.Tools of data collection: Emotional intelligence knowledge questionnaire, emotional intelligence questionnaire, critical thinking questionnaire and self-esteem scale.Results: 18.3% of nurse students had satisfactory knowledge regarding total emotional intelligence before the intervention which improved significantly to (96.7%) immediately after the program and decreased in follow up phase to (38.3 %).Also, more than half of nurse students had low emotional intelligence level before the program which increased at the post intervention phases, reaching (51.7%), (66.7%) respectively. In addition, more than one quarter of nurse students had moderate critical thinking skills level (26.7%) at the pre intervention phase. It increased at the post intervention phase, reaching (83.3%) and decreased in follow up phase to reach (66.7%). Minority of nurse students had high level of self-esteem (1.7%). The percentage had increased significantly at the post intervention phase, reaching (63.3%) and decreased in follow up phase to (36.7%).Conclusion: The improvement of nurse students emotional intelligence enhanced their critical thinking skills and self-esteem.Recommendations: Creating emotionally friendly teaching environment for nurse students, integrate emotional intelligence courses into the nursing curriculum to increase nurse students development, and enhance education by critical thinking approach.